Prevalence of Fatigue and Its Association With Quality of Life Among Frontline Clinicians in Ophthalmology and Otolaryngology Departments During the COVID-19 Pandemic - Jin, Yu; Li, Yue; Li, Xiu-Ya; Zhao, Yan-Jie; Cheung, Teris; Ungvari, Gabor S.; Li, Michael; An, Feng-Rong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has caused psychological distress and heavy burden in medical professionals. This study examined the prevalence of fatigue and its association with quality of life (QOL) in clinicians working in ophthalmology and otolaryngology departments during the COVID-19 pandemic in China. Methods: This was a cross-sectional national online survey conducted between March 15 and March 20, 2020 in China. The severity of fatigue, depression and QOL were measured using the Numeric Rating Scale (NRS), the 9-item Patient Health Questionnaire (PHQ-9), and the World Health Organization Quality of Life Questionnaire-Brief Version (WHOQOL-BREF), respectively. Results: In total, 3,912 clinicians completed the survey (2,155 in ophthalmology department, and 1,757 in otolaryngology department); 2,049 [52.4%; 95% confidence interval (CI) = 50.8–53.9%] reported fatigue (NRS score ≥ 4). Multiple logistic regression analysis revealed that junior clinicians [Odds ratio (OR) = 0.82, 95% CI = 0.68–1.00, P = 0.045] had lower risk of fatigue; while clinicians working in tertiary hospitals (OR = 1.23, 95% CI = 1.02–1.49, P = 0.029), and the presence of more severe depressive symptoms (PHQ-9 total score ≥ 5; OR = 7.40, 95% CI = 6.29–8.70, P < 0.001) were independently associated with higher risk of fatigue. After controlling for covariates, clinicians with fatigue had significantly lower QOL compared with those without [F(1, 3, 911) = 283.75, P < 0.001]. Conclusion: Fatigue was common in clinicians working in ophthalmology and otolaryngology departments during the COVID-19 pandemic. Considering the negative impact of fatigue on clinicians' QOL, health authorities and policymakers should conduct regular screening for fatigue and develop preventive strategies for frontline clinicians working under excessive stress.